ANALISIS KETERAMPILAN MENULIS CERPEN SISWA KELAS V SDN 16 CAKRANEGARA - Wahyu Tanata; Safruddin Safruddin; Syaiful Musaddat (Program Studi PGSD, FKIP, Universitas Mataram, 2021)
This study aims to describe the skill level of fifth grade students at SDN 16 Cakranegara in writing short stories. In this study, a qualitative approach was applied using descriptive qualitative methods. One form of assessment on students' short story writing skills is to look at the completeness of the intrinsic elements in students' short stories. The source of data in this study is the work of students' short stories, totaling 27 short stories. The results of students' short stories writing were analyzed and described based on the intrinsic elements of the short story, namely the theme, character, setting, plot, and mandate. Based on the benchmarks for the assessment of students' short stories writing skills, they are categorized as very good, good, sufficient, lacking, and very poor. The results of the analysis of short story writing skills, students who are categorized as very good are 11 students with a percentage of 40.74%. There are 4 students in good category with a percentage of 14.81%. There are 4 students who are categorized as sufficient with a percentage of 14.81%. Students who are categorized as less are 7 students with a percentage of 25.92% and 1 student gets a very poor category with a percentage of 3.70%. Thus, it can be concluded that the short story writing skills of the fifth grade students of SDN 16 Cakranegara are in good category, according to the calculation of the total score of 1883 with an average score of 69.74. This study also provides recommendations for teachers to be more active in providing writing exercises to students, especially writing short stories so that students' short stories writing skills are better. and for further researchers to analyze the short story writing skills of elementary school students in other classes.